An Analysis of Teacher’s Strategies in Teaching Speaking - Aisyah Nurbaktiah; Syafrizal Sabaruddin; Dedy Sofyan (Yayasan Karinosseff Muda Indonesia, 2021)
The objectives of the research were to find out the strategies used by teachers in teaching speaking at SMAN 5 Kota Bengkulu and to describe how the teachers implement the strategies in the teaching process. This research was descriptive qualitative. The subjects were two English teachers who taught at tenth grade. The data were collected by using field notes and video documentation and were analyzed by using four procedures by Miles and Huberman namely data collection, data reduction, displaying data, and conclusion. The results showed that teacher 1 used seven strategies from twelve speaking strategies and teacher 2 used eight speaking strategies. The strategies used were Task Completion (50%), Opinion Sharing (83.3%), Information Transfer (16.6%), Reasoning Gap (33.3%), Questioning (100%), Brainstorming (33.3%), Scaffolding (100%), and Drilling (66.6%). Meanwhile, the other four speaking strategies were not used such as Information Gap, Jigsaw, Information Gathering, and Role Play. For the implementation, the teachers gave explanation and instruction to the students before applying the strategy. The teachers asked the students to work in pairs or groups which made them to communicate in English. In short, although the name of the strategy used by teachers was similar to each other, but the steps or ways carried out by them was different from one teaching to another. Furthermore, the teachers applied the strategies based on students’ condition, need, and material in order to help students become more active in the process of teaching and learning.